From old slavery to new forms of exploitation: A reflection on the conditions of irregular migrant labour after the Chowdury case. Issue 3 (September 2019) - Lucifora, Annalisa
The spread of exploitative working practices requires an in-depth reflection on the impact of the free market and global competitiveness on some fundamental rights that are inherent to all human beings. After an investigation into the conditions that have led to an exponential increase in the exploitation of illegal migrant labour, the article focuses on the system of legal protection set by the European Convention on Human Rights (ECHR), which in Article 4 only prohibits slavery and servitude (para 1) and forced and compulsory labour (para 2). It could raise the question of where to put those conducts that, although they are manifestly inconsistent with fundamental rights, they do not, however, easily conform to any of the labels expressly laid out in Article 4 ECHR. The issue has recently been put under the spotlight by the Chowdury case, where the analysis of the extremeness of the working conditions allows the Court to rule out any relevance of the element of consent. This interpretation would allow the most serious cases of exploitation to be brought within the scope of forced labour and thus to expand the protection offered by Article 4 ECHR.